Interviewing Suspects in Denial: On How Different Evidence Disclosure Modes Affect the Elicitation of New Critical Information - May, Lennart; Granhag, Pär Anders; Tekin, Serra (Frontiers in Psychology, 2017)
This study examines how different evidence disclosure modes affect the elicitation of new critical information. Two modes derived from the Strategic Use of Evidence (SUE) framework were compared against an early disclosure mode (i.e. the evidence was disclosed at the outset of the interview). Participants (N = 88) performed a mock crime consisting of several actions before they were interviewed as suspects. In both SUE conditions the interviewer elicited and disclosed statement-evidence inconsistencies in two phases after an introductory phase. For the SUE-Confrontation (SUE-C) condition, the interview was introduced in a business-like manner, and the interviewer confronted the suspects with the in/consistencies without giving them a chance to comment on these. For the SUE-Introduce-Present-Respond (SUE-IPR) condition, the interviewer introduced the interview in a non-guilt-presumptive way, presented the in/consistencies and allowed the suspects to comment on these, and then responded to their comments; at all times in a non-judgemental manner. Both SUE conditions generated comparatively more statement-evidence inconsistencies. The SUE-IPR condition resulted in more new critical information about the phase of the crime for which the interviewer lacked information, compared to the Early disclosure condition. A likely explanation for this was that (for the SUE-IPR condition) the interviewer used the inconsistencies to create a fostering interview atmosphere and made the suspects overestimate the interviewer’s knowledge about this phase of the crime. In essence, this study shows that in order to win the game (i.e. obtaining new critical information), the interviewer needs to keep the suspect in the game (i.e. by not being too confrontational and judgemental).